A Catalyst with Two‐Coordinate Nickel: Theoretical and Catalytic Studies1. Issue 5 (23rd January 2014) - Mondal, Kartik Chandra; Samuel, Prinson P.; Li, Yan; Roesky, Herbert W.; Roy, Sudipta; Ackermann, Lutz; Sidhu, Navdeep S.; Sheldrick, George M.; Carl, Elena; Demeshko, Serhiy; De, Susmita; Parameswaran, Pattiyil; et al.
Abstract: The bisadduct (cAAC)2 Ni II Cl2 [1 ; cAAC = cyclic (alkyl)(amino)carbene] was directly synthesized by treating cAAC with NiCl2 . Compound1 was reduced to (cAAC)2 Ni 0 (2 ) by using lithium diisopropylamide or KC8 . Crystals of2 were stable under an inert gas for several months and decomposed upon heating above 165 °C. On the basis of the calculated natural bond orbital charge values of the nickel atom in2, the oxidation state of nickel was determined to be between Ni I and Ni 0 (+0.34). Theoretical calculations suggested a closed‐shell singlet electronic configuration of2 with little biradical character. Ab initio multiconfigurational C(R)ASSCF/CASPT2 calculations predicted a closed‐shell singlet electronic configuration (Ni 0 ), whereas excited spin states possessed Ni I character with unpaired electrons on neighboring carbon atoms. The catalytic activity of complex2 was investigated for the homocoupling of various unactivated aryl chlorides/fluorides. The biaryls were obtained in good yields at moderate temperature. Theoretical studies showed that an intermediate containing Ni III was more favored than one with Ni IV . Abstract : The synthesis of (cAAC)2 Ni II Cl2 (1 ) and its conversion into (cAAC)2 Ni (2 ) through reduction is reported [cAAC = cyclic (alkyl)(amino)carbene]. Efficient reductive homocoupling of unactivated aryl chlorides and fluorides is catalyzed by2 through C–Cl and C–F bond activation. Detailed high‐level theoretical investigations are performed to understand the electronic and catalytic cycle of2 .